The Effect Of Good Corporate Governance (GCG), Corporate Social Responsibility (CSR) Disclosure, And Intellectual Capital On Tax Avoidance: (Empirical Study on Transportation and Logistics Companies Listed on the Indonesia Stock Exchange for the 2019-2021 Period) - Novri Rahmi; Azwirman; Novriadi (Jurnal Akuntansi, 2024)
Tax avoidance is a legal and safe strategy for taxpayers, since it does not conflict with the established tax terms. This study aims to test and analyze the effect of corporate governance by selecting variabel of the board of independent commissioners and auditing committees, disclosure of social responbility and intellectual capital on tax evoidance on transport and logistics companies registered at the Indonesian stock exchange 2019-2021. The study includes quantitative work with an associative approach that uses detailed financial statements annully. The population of the study included 30 transport and logistics companies listed in the Indonesia stock exchange period 2019-2021. Research sample were selected using purposive sampling technique to be obtained by 10 companies that met the study criteria over a time span of 20192021. Data analysis uses a double linear regression analysis techniques in which result significantly variable independent council of commissioners, auditing committees, and disclosure of social responbility do not affect tax avoidance. Whereas intellectual capital variables have significant impact on tax avoidance. Simultaneous variables of the independent council of commissioners, auditing committees, disclosure of social responbility and intellectual capital affect tax avoidance.